A review of friction stir welding pin profile - Emamian, S. (Springer Heidelberg, 2017)
Friction stir welding (FSW) is a solid state joining process where the joint occurs below the melting point of the base metal. Recently, not only soft materials but also high melting materials have been given an attention in FSW research activities. There are many studies on high melting materials such as steel, titanium, and inconel. There are different parameters which contribute to the joint quality. Many researchers have studied on the traverse and rotational speeds as the main process parameters in order to obtain optimum weld quality. Tool geometry is another important parameter that has an influence on the weld quality. This paper aims to review the development of various pin profiles and its effects to the microstructure and mechanical properties of the weld joint. Based on the published papers, square pin profile produced sound joints. However, in other studies threaded cylinder or threaded taper provides better joints. Above all, there is an equal result among all studies in which threaded shapes are most effective on tool performance. © Springer Nature Singapore Pte Ltd. 2017.